PENGARUH RUBBER BALL TRAINING TERHADAP PENINGKATAN KEKUATAN MENGGENGGAM PADA LANSIA DIABETES MELLITUS DI PERSADIA CIPAYUNG - Achirda, Nur; Sudarsono, Ari; Puspitaningtias, Dzaky Aulia (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Elderly with DM for a long time generally have a poor quality of life because it has a negative impact on the physical and psychological aspects of the sufferer. Due to the detrimental effects of hyperglycemia on nerves and connective tissue, hand function in terms of dexterity, hand grip strength and pinching, hand skills can be impaired so that quality of life, independence and activity in the elderly can be disrupted. Purpose to determine the effect of rubber ball training on increasing grip strength in DM elderly at Persadia Cipayung. Method is pre-experiment with One Group Pre-test Post-test design. This research was conducted in April - May 2023. Sampling used a purposive sampling method with a total sample of 32 people. The results showed that the average grip strength before the intervention was 15.08 and after that it was 16.75 with a maximum value of 21.4. The result of the p value is 0.000 (p < 0.05). Conclusion there is an effect of rubber ball training on increasing the grip strength of elderly DM in Persadia Cipayung.